1978
DOI: 10.1088/0022-3727/11/2/003
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the barrier height in metal-CdF2Schottky diodes

Abstract: Schottky diodes on highly conducting CdF2 crystals have been produced with Au and Al metals electrodes. Based upon internal photoemission, capacitance and I(V) measurements, the metal-CdF2 zero-field barrier heights were determined. The average values are 1.45 eV for the Au electrode and 0.82 eV for the Al electrode. The electron affinity of the chemically etched CdF2 was estimated to be 3.6 eV in agreement with the value derived from the measurements of external photoemission, 4.1 eV. The interface properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…As reported [3,6], the presence of a foreign material (e.g., polymeric compatibilizer, microfiller or nanofiller) can affect the crystallization behavior of semicrystalline polymers including PP. However, only few studies have focused on the effect of foreign materials on the polymorphism of such polymers and the formation of the less common crystalline structure forms [7][8][9]. It has been shown that the introduction of only 0.5 wt% of N, N 0 -dicyclohexylo-2,6-naphthaleno dicarboxy amide as b-phase nucleating agent leads to the formation of almost 100% b-crystalline phase in isotactic PP, with a significant changes of the structure, morphology, and properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…As reported [3,6], the presence of a foreign material (e.g., polymeric compatibilizer, microfiller or nanofiller) can affect the crystallization behavior of semicrystalline polymers including PP. However, only few studies have focused on the effect of foreign materials on the polymorphism of such polymers and the formation of the less common crystalline structure forms [7][8][9]. It has been shown that the introduction of only 0.5 wt% of N, N 0 -dicyclohexylo-2,6-naphthaleno dicarboxy amide as b-phase nucleating agent leads to the formation of almost 100% b-crystalline phase in isotactic PP, with a significant changes of the structure, morphology, and properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…␤ modification, different in its physical and mechanical properties from ␣ modification to some degree, is obtained at about 130°C, the most favorable temperature for ␤ growth, [5][6][7][8] and a high content of ␤ crystals can be acquired under special conditions, such as the quenching of the melt within a certain temperature range, 9,10 directional crystallization in a temperature gradient field, 11 shear-induced crystallization, 12 or dop-ing of the resin with certain heterogeneous nucleating agents. [13][14][15] Previous publications have commonly reported that ␤ modification is less stable than ␣ modification, tending to transform into ␣ modification when heated within a certain temperature range 16 or stretched. 17 Compared with ␣ modification, ␤ modification is more ductile and easier to stretch, and it has a higher Vicat softening temperature, whereas the tensile yield strength of ␣ modification is higher, the neck formation in a stress-strain test is more obvious, and the strain hardening is delayed.…”
Section: Introductionmentioning
confidence: 99%
“…For this kind of comparison we need to know the positions of the band edge in the absolute energy scale relatively to the vacuum level. The absolute position of the conduction band edge was determined in the photoemission yield experiment for CdF2 : Y [9] and for internal photoemission measurements [8]. The absolute position of the valence band edge was determined in UPS results presented in this paper.…”
Section: Introductionmentioning
confidence: 99%